Role of the Structural and Thermal Peclet Numbers in the Brass Continuous Casting - Kwapisiński P.; Lipnicki Z.; Ivanova A. A.; Wołczyński W. (Archives of Foundry Engineering, 2017)
The Structural Peclet Number has been estimated experimentally by analyzing the morphology of the continuously cast brass ingots. It allowed to adapt a proper development of the Ivantsov’s series in order to formulate the Growth Law for the columnar structure formation in the brass ingots solidified in stationary condition. Simultaneously, the Thermal Peclet Number together with the Biot, Stefan, and Fourier Numbers is used in the model describing the heat transfer connected with the so-called contact layer (air gap between an ingot and crystallizer). It lead to define the shape and position of the s/l interface in the brass ingot subjected to the vertical continuous displacement within the crystallizer (in gravity). Particularly, a comparison of the shape of the simulated s/l interface at the axis of the continuously cast brass ingot with the real shape revealed at the ingot axis is delivered. Structural zones in the continuously cast brass ingot are revealed: FC - fine columnar grains, C - columnar grains, E - equiaxed grains, SC - single crystal situated axially.